Overcoming binder limitations of sheet-type solid-state cathodes using a solvent-free dry-film approach - Hippauf, Felix; Schumm, Benjamin; Doerfler, Susanne; Althues, Holger; Fujiki, Satoshi; Shiratsuchi, Tomoyuki; Tsujimura, Tomoyuki; Aihara, Yuichi; Kaskel, Stefan (Energy Storage Materials, 2019)
All-solid-state lithium-ion batteries are promising candidates to overcome safety and energy limitations of common lithium-ion batteries. Although excellent results have been reported for sulfide based electrolytes on a small scale, classical slurry-based lithium-ion processing fails to reproduce the same performance in a larger cell. In this study, a dry-film (DF) process is presented that replaces slurry based binders by a fibrous PTFE binder and reduces the binder amount to an absolute minimum as low as 0.1 wt%, which is the lowest reported value so far. Free-standing NCM sheets with a high areal loading of 6.5 mAh cm−2 were prepared showing even at room temperature the same rate performance like binder-free electrodes with 2.5 mAh cm−2. The impact of binder content on cell performance has been studied revealing significantly reduced impedance at contents below 0.7 wt%. To realize a practical cell, the cell composition was optimized and a 9 cm2 sized rocking-chair type all-solid-state battery was prepared without any solvents underlining the sustainability of the DF process. The battery was cycled for 100 cycles without any artificial pressure, demonstrating the versatility and potential of the DF process.
CRIS-Team Scopus Importer:2022-04-14
Keywords: All-solid-state battery; Electrode sheet; Low binder amount; Solid electrolyte; Solvent-free processing; Thiophosphate electrolyte